2020
DOI: 10.3390/ani10091476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prickly Pear Cactus Peel Supplementation on Milk Production, Nutrient Digestibility and Rumen Fermentation of Sheep and the Maternal Effects on Growth and Physiological Performance of Suckling Offspring

Abstract: Prickly pear cactus peels (Opuntia ficus-indica, PPCP) are sustainable byproducts available in arid regions and a rich source of antioxidants. Fifteen multiparous Barki ewes (2–3 years old, 46.94 ± 0.59 kg body weight, BW) at postpartum were individually distributed in three equal groups and fed diets supplemented with PPCP at doses of 0, 5 and 10 g/head/day. Lambs were individually distributed into three equal groups according to their mothers’ groups to investigate the maternal effect on lambs’ growth perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Several studies have been performed to investigate the effect of Opuntia cladodes as forage on livestock performance and rumen physiology [18,60,61].…”
Section: Effect On Animal Performancementioning
confidence: 99%
“…Several studies have been performed to investigate the effect of Opuntia cladodes as forage on livestock performance and rumen physiology [18,60,61].…”
Section: Effect On Animal Performancementioning
confidence: 99%
“…Forage cactos as Opuntia and Nopalea are a perennial crop, developed in several semiarid regions [1]. During periods of drought, it is used as forage in countries such as United States, Mexico, South Africa, Australia, Tunisia, Egypt, and Brazil [1][2][3][4]. In Brazil, It was introduced in 1880 and it is considered the main source of feed for herds, mainly in the semiarid region [1,5,6].…”
Section: Stand Productivity and Spacingmentioning
confidence: 99%
“…This was also reflected by higher ADG on heifers fed commercial and control diets, which attained a higher DMI compared to those fed cactus diets. The observed low DMI and ADG for heifers fed cactus diets could be attributed to polyphenols, such as condensed tannins, phytates and oxalates [31]. Morshedy et al [31] also reported a low DMI of cactus diets relative to non-cactus feeds in sheep fed 5 and 10 g/head/day.…”
Section: Cost Effectiveness For Drought Scenariomentioning
confidence: 99%
“…The observed higher FCR for heifers fed cactus diets was due probably to higher fibre content in these diets. Because cactus cladodes contain secondary compounds [31], it is highly likely that the degradation of the cactus material during digestion was low, resulting in low average daily gain and final body weight gain.…”
Section: Cost Effectiveness For Drought Scenariomentioning
confidence: 99%